Penguatan Kapasitas Nasional Dalam Teknologi Bawah Air: Strategi Riset, Industri, dan Kolaborasi Akademik - Muhsin Kahar (Riset Sains dan Teknologi Kelautan, 2026)
As the world’s largest archipelagic country, Indonesia has a pressing strategic interest in mastering underwater technologies to effectively manage marine resources, strengthen national defense, and mitigate maritime disasters. However, a significant technological gap remains between Indonesia and developed countries in this domain. This study aims to formulate a comprehensive strategy to enhance national capacity in underwater technology. Using a descriptive qualitative approach and literature review, this paper examines four key aspects: (1) analysis of the underwater technology gap; (2) the urgency of developing laboratory infrastructure, certification systems, and human resource competencies; (3) the Triple Helix collaboration model involving universities, industry, and government; and (4) the formulation of a national technology development roadmap. The findings indicate that technological self-reliance can only be achieved through strong synergy among research institutions as innovation hubs, industry as manufacturers and off-takers, and government as both facilitator and regulator. The proposed roadmap encompasses phases of foundational capacity building, research downstreaming, and ultimately achieving technological independence and global commercialization in alignment with the Indonesia Emas 2045 vision.